Neurological Deficits of Coronavirus Disease-19: A Systematic Literature Review - Fawaz Al-Hussain, Muhammad Hashim Ghouri, Zouina Sarfraz, Noor Ul Falah, Saima Tabassum, Ambreen Anjum, Mah Rukh (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To review neurological aspects of patients infected with COVID-19 including neurological dysfunctions and possible pathophysiology. Methods: A systematic review of articlesfrom PubMed, Ovid MEDLIN, DOAJ databases and grey literature included the WHO-COVID-19 database, and medRxiv.Articles published from January 2020 until June 2020 were included in the review. Out of the226 titles and abstracts, 213 were identified after the removing duplicates. With a screening of 119 studies carried by all authors, 83 full-text articles were assessed based on inclusion criteria of the neurological perspectives with COVID-19. Subsequently, 45 texts were removed. A total of 38 studies were included in the last scrutiny.Specifically, case reports, cohort studies, and case series were included Results: Reviewed evidence was presented in textual and tabulated format, which includes methodology, characteristics of included studies and summary of findings. Correlational evidence of COVID-19 disease and neurological dysfunctions with possible pathophysiology isreviewed. Conclusion:The findings provide evidence for physicians and neurologists working with COVID-19 patients about the possible probable complications and clinical presentations due to the SARS-CoV-2 infection.